Kepemimpinan Kepala Sekolah dalam Implementasi Manajemen Berbasis Sekolah di SMA Al-Masthuriyah - Andrianto (STAI Terpadu Yogyakarta, 2020)
One of the educational problems that our nation is currently facing is the issue of the quality of education. Various attempts have been made to improve the quality of national education, including through various training and improvement of teacher competencies, procurement of books and learning tools, improvement of educational facilities and infrastructure, and improving the quality of school management. Leadership is one of the factors that determine the successful implementation of SBM. School Based Management gives flexibility to schools to manage their potential by involving all elements of stakeholders to achieve improvements in the quality of the school. Because schools have very broad authority, the presence of a leader figure is very important. An understanding of the nature of leadership. In implementing SBM, School Based Management gives flexibility to schools to manage their potential by involving all elements of stakeholders to achieve improvements in the quality of the school. Because schools have very broad authority, the presence of a leader figure is very important. An understanding of the nature of leadership. In implementing SBM, principals need to have strong, participatory, and democratic abilities. This research uses a qualitative approach in descriptive form. The use of descriptive methods in this study with the aim to describe an activity of implementing the leadership of the school principal in implementing school-based management which first analyzes the implementation process. The implementation of School Based Management (SBM) at Al-Masthuriyah Sukabumi High School is participatory. This management gives authority from the foundation to the school, and then the school delegates to each teacher and employee. All teachers and employees feel involved starting from planning, implementing, and evaluating school programs. The principle of decentralization considers that the problems that arise in schools will be adjusted as well as possible if the solution is left to the party closest to the existence of the problem. In resolving the problem of education in schools, the most knowledgeable about the problem are the residents of the school itself, especially teachers, staff, school principals and parents of students. The application of participatory management improves the quality and education services so that Al-Masthuriyah High School can compete and produce quality graduates both academically and non-academically. SBM will succeed well if school members have the initiative in carrying out their work and the initiative of each individual is appreciated. What happened at Al-Masthuriyah High School was the lack of school community initiative due to lack of ownership of the school.